Trade wars and tech giants: The U.S.–China policy effect on American technology companies - Henrika, Margareth; Ariswati, Lusiana Desy; Kesuma, Muhammad Ramadhani; Widaryo, Chandika Mahendra; Irianto, Ellen D Oktanti; Aini, Rohana Nur (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
The tariff policies implemented by the United States government on imported products from China—particularly technology-related goods—have significantly impacted the global technology sector. This study aims to analyze the influence of U.S.–China tariff policies on American technology companies, with a specific focus on changes in production costs and the operational strategies adopted in response. Employing a qualitative approach through case studies and literature review, the research explores how these tariff measures have affected the performance of U.S. tech firms. The findings reveal that the tariffs have led to increased operational costs, resulting in reduced profit margins and heightened stock price volatility. Large corporations with greater resources tend to better withstand these impacts through supply chain diversification and operational efficiency, while smaller firms face greater challenges. On the other hand, these trade policies have also spurred innovation and strategic restructuring within the tech sector, as major firms invest in automation and process optimization. The study offers insights into mitigation strategies that tech companies can adopt to navigate the effects of volatile international trade policies. These findings hold important implications for strategic decision-making in the face of ongoing global trade uncertainties.